THE IMPACT OF PROFESSIONAL EXPERIENCE ON COLLECTIONS MANAGEMENT: HOW SEVENTEEN YEARS IN THE FIELD SHAPE DECISIONS AND STRATEGY EFFECTIVENESS (International Seven Journal of Multidisciplinary, 2022)
This article examines how seventeen years of professional experience in collections management influences decision-making and the effectiveness of recovery strategies. Drawing on organizational learning theory, behavioral insights, and credit risk analytics, it demonstrates that long tenure fosters empirically informed heuristics, enhances the calibration of risk models, and improves the orchestration of contact strategies. Experienced managers translate daily operational insights into stable routines, optimize incentive structures, and balance short-term recovery with compliance and reputational sustainability. Their extensive exposure to economic cycles, regulatory change, and portfolio shocks strengthens scenario planning and governance practices, while also reinforcing the importance of ethical, consumer-centered approaches. The findings suggest that accumulated professional experience not only enhances strategic adaptability and analytical rigor but also ensures that collections practices remain effective, compliant, and respectful of consumer dignity.